PENGARUH PEMBERIAN KOMPOS SISA BIOGAS KOTORAN SAPI TERHADAP PERBAIKAN BEBERAPA SIFAT FISIK ULTISOL DAN HASIL KEDELAI (Glycine max (L.) Merill) - ,, Refliaty; Tampubolon, Gindo; ,, Hendriansyah (Jurnal Hidrolitan, 2011)
ABSTRACTThe objectives of research were to study influence of biogass compost from cow manure for improvement some physical properties of Ultisol and Soy bean yield. The research was conducted from Janary 2011 untill April 2011. Design of experiment was randomized completely block design with 6 treatment (dossage of biogass compost from cow manure) and 4 replication. The treatment were SB0 : without treatment, SB1 = 5 ton ha-1, SB2 = 10 tone ha-1, SB3 = 15 tone ha-1, SB4 = 20 tone ha-1, SB5 = 25 tone ha-1. Data was analyzed by varians analysis and Duncan New Multiple Range Test on Î± = 0,05. The results of research was show that biogass compost from cow manure was not affect significantly on soil organic matter, porosity total, and penetration, but it was affect significantly on soil water content increasing. Dossage 20 tone ha-1 of Biogass compost from cow manure can increase soy bean yield until 1,083 tone ha-1 and the best dossage for Ultisol.